Adolescent voices speak out: if only they would - if only they could : a case study : the interplay between linguistic and strategic competence in classrooms where modern languages are used - Coyle, Do (1999)
This thesis focuses on groups of adolescent learners in two comprehensive schools. It explores the interplay between linguistic and strategic competence in classrooms where a foreign language is used i e. in French or Spanish lessons and in geography classes where the foreign language is also used as a medium for instruction. In Part 1, the research is positioned within a contextual, conceptual and theoretical framework, underpinned by Vygotskian socio-cognitive principles. Part 2 consists of an ethnographic-oriented.case study at two sites. The study uses methodological triangulation to co-construct the learning environments from different perspectives, based on document analysis, questionnaires, interviews, lesson observations and the microgenetic analysis of student interaction during linguistic tasks analysed at both an inter- and intramental level. The thesis is built on the metaphor of language games and identifies strategic and linguistic moves which could potentially bring about changing the rules in order to enable an alternative game to played. The thesis leads the writer to argue for a re-conceptualisation of learner strategies based on the notion of ‘strategic classrooms’ and recommends the integration of ‘alternative’ linguistic and strategic ‘moves' into everyday classroom practice if learners are to find a ‘voice’.